(x+2y-1)dx+3(x+2y)dy=0

Simple and best practice solution for (x+2y-1)dx+3(x+2y)dy=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+2y-1)dx+3(x+2y)dy=0 equation:


Simplifying
(x + 2y + -1) * dx + 3(x + 2y) * dy = 0

Reorder the terms:
(-1 + x + 2y) * dx + 3(x + 2y) * dy = 0

Reorder the terms for easier multiplication:
dx(-1 + x + 2y) + 3(x + 2y) * dy = 0
(-1 * dx + x * dx + 2y * dx) + 3(x + 2y) * dy = 0

Reorder the terms:
(-1dx + 2dxy + dx2) + 3(x + 2y) * dy = 0
(-1dx + 2dxy + dx2) + 3(x + 2y) * dy = 0

Reorder the terms for easier multiplication:
-1dx + 2dxy + dx2 + 3dy(x + 2y) = 0
-1dx + 2dxy + dx2 + (x * 3dy + 2y * 3dy) = 0
-1dx + 2dxy + dx2 + (3dxy + 6dy2) = 0

Reorder the terms:
-1dx + 2dxy + 3dxy + dx2 + 6dy2 = 0

Combine like terms: 2dxy + 3dxy = 5dxy
-1dx + 5dxy + dx2 + 6dy2 = 0

Solving
-1dx + 5dxy + dx2 + 6dy2 = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'd'.
d(-1x + 5xy + x2 + 6y2) = 0

Subproblem 1

Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0

Subproblem 2

Set the factor '(-1x + 5xy + x2 + 6y2)' equal to zero and attempt to solve: Simplifying -1x + 5xy + x2 + 6y2 = 0 Solving -1x + 5xy + x2 + 6y2 = 0 Move all terms containing d to the left, all other terms to the right. Add 'x' to each side of the equation. -1x + 5xy + x2 + x + 6y2 = 0 + x Reorder the terms: -1x + x + 5xy + x2 + 6y2 = 0 + x Combine like terms: -1x + x = 0 0 + 5xy + x2 + 6y2 = 0 + x 5xy + x2 + 6y2 = 0 + x Remove the zero: 5xy + x2 + 6y2 = x Add '-5xy' to each side of the equation. 5xy + x2 + -5xy + 6y2 = x + -5xy Reorder the terms: 5xy + -5xy + x2 + 6y2 = x + -5xy Combine like terms: 5xy + -5xy = 0 0 + x2 + 6y2 = x + -5xy x2 + 6y2 = x + -5xy Add '-1x2' to each side of the equation. x2 + -1x2 + 6y2 = x + -5xy + -1x2 Combine like terms: x2 + -1x2 = 0 0 + 6y2 = x + -5xy + -1x2 6y2 = x + -5xy + -1x2 Add '-6y2' to each side of the equation. 6y2 + -6y2 = x + -5xy + -1x2 + -6y2 Combine like terms: 6y2 + -6y2 = 0 0 = x + -5xy + -1x2 + -6y2 Simplifying 0 = x + -5xy + -1x2 + -6y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

d = {0}

See similar equations:

| g(x)=2x^5+5x^4+3x^3+16x^2+4x+8 | | x^2+x=-5 | | 6x-7=13x | | -.5b=-8 | | 13c+40=8c-20 | | .75t=-15 | | 24*(1/2+x)=4 | | x^2-155x+(2135.71)= | | 8(4+x)=2x+65 | | -.75z=-5.5 | | n-2=13+6n | | .25x=.25-0.375x | | -5*(19+x)=0 | | x^2-18x+90=0 | | -.67t=-16 | | x^2-6x-(0.222)= | | n-(-6)=-12 | | t-2=.5 | | ln(4x-7)=11 | | 4x+5=2x+53 | | 6w=9w+15 | | -.2y=-6 | | K+1-4(2k-9)=0 | | x^2-6x+(0.222)= | | -.8x=-16 | | -35x^2+44x+7=0 | | 0=.8d | | x^3-40=24 | | -6+5(8-k)-8k=0 | | -45+14z-z^2=0 | | 3x-3+3=12 | | m-4=-75 |

Equations solver categories